The Development of Islamic Stok Mutual Funds In Indonesia Before and During The COVID-19 Pandemic - Sukoco Edi Sasmito (Journal of Finance and Islamic Banking, 2021)
Sharia mutual funds are one of the sharia investment products or instruments that people can choose to invest in, mainly the type of Islamic equity mutual funds. This paper aimed to analyze the development of Islamic equity funds in Indonesia. In this paper, the analysis method used is descriptive statistics using the Microsoft Excel 2016 analysis tool. Based on the data processing results, Islamic stock mutual funds in Indonesia still had minimal interest from investors compared to conventional equity mutual funds. In addition, other types of equity mutual funds in the form of Sharia ETFs also still have minimal interest from investors. It is hoped that sharia equity mutual fund practitioners can improve the performance of their mutual funds so that many investors will be interested in investing in Islamic equity mutual funds.